Descripcion de dos nuevos cultivares de mani (Arachis hypogaea L. subsp. hypogaea var. hypogaea) - Soave, J.H.=700 1 Blanco, C.A.; Kraus, T.A.
(Es, En)
ilus., 9 ref.
Keywords: ARACHIS HYPOGAEA; VARIEDADES; CALIDAD; TAMAÑO; SEMILLAS; CONTENIDO DE LIPIDOS; ARGENTINA